Glyphosate applied at a hormetic dose improves ripening without impairing sugarcane productivity and ratoon sprouting - de Almeida Silva, Marcelo [UNESP]; Espinoza Véliz, José Gerardo; Pereira Sartori, Maria Márcia [UNESP]; Luiz Santos, Hariane [UNESP] (Elsevier, 2022)
The management of sugarcane ripening is essential to ensuring the supply of high-quality raw material for the sugar-alcohol industry; chemical ripeners are frequently used to accelerate sucrose accumulation in the stalks during harvesting. The potential ripening effect of a low dose of glyphosate was evaluated in sugarcane, along with its impact on productivity and sprouting in the next crop cycle. A field experiment was conducted in 2015 and 2016 using a randomized block design with eight replicates in a split-plot scheme, with the following treatments: (1) control with only water application, (2) glyphosate at a low dose of 1.8 g a.e. ha−1 (corresponding to 0.005 L ha−1 of the commercial product (cp)), and (3) glyphosate at the commercially recommended dose for a ripener at 180 g a.e. ha−1 (corresponding to 0.50 L ha−1 of the cp) applied at 60, 45, 30, and 15 days before harvest (DBH). The harvest was performed on May 25, 2016 (0 DBH), and a total of five periods were evaluated. This study showed that the application of a hormetic dose of glyphosate to stimulate sugarcane ripening is promising, despite the limited duration of the effect. The application of the hormetic dose (1.8 g a.e. ha−1) at 30 DBH improved the technological quality of sugarcane in terms of Brix% juice, pol% cane, purity% juice, moisture% cane, reducing sugars, total reducing sugars, and total recoverable sugar. Additionally, it increased pol productivity, and did not affect ratoon sprouting in the subsequent cycle. Thus, this study provides a strategy for ripening management with a low environmental impact for sugarcane producers through a low (hormetic) dose of glyphosate.
Keywords: Herbicide; Hormesis; Pol% cane; Saccharum spp.; Tillering; Yield